COMMUNICATION ETHICS IN ONLINE LEARNING THROUNGH THE ZOOM APPLICATION IN SOCIAL SCIENCES FACULTY - Novi Sulianti; Asnawati Asnawati; Yanto Yanto (SENGKUNI Journal (Social Science and Humanities Studies), 2021)
This study aims to determine the ethics of student communication to lecturers and student ethics to fellow students in online learning through the zoom application for students of the Faculty of Social Sciences. This research method is fleld research with a qualitative approach. The data was collected by means of observation, interview and documentation techniques. The theory used in this study is Burhannudin Salam's Communicating Ethics, descriptive and normative. Descriptive Ethics is about values and patterns of human behavior as a fact, while Normative Ethics talks about norms or rules that guide human behavior. The sources of this research were students and students of the Faculty of Social Sciences, Dehasen University Bengkulu. The results show that there are still some people who do not follow the rules and ethics of student communication to lecturers during lectures through the zoom application, while the ethics of students towards fellow students when taking lectures through the zoom application is quite good even though there are still some students who still do not use ethics properly to fellow students during lectures through the zoom application in progress.